Associations Between Metabolic Profiles and Target-Organ Damage in Chinese Individuals With Primary Aldosteronism - Zhang, Shao-Ling; Gao, Jing-Wei; Guo, Ying; Feng, Qi-Ling; Tang, Ju-Ying; Yan, Li; Wang, Jing-Feng; Cheng, Hua; Liu, Pin-Ming (Frontiers in Endocrinology, 2020)
Purpose: Patients with primary aldosteronism (PA) have an increased risk of target-organ damage (TOD), but whether metabolic syndrome (MetS) is more prevalent and contributes to TOD in PA patients remains unresolved. We aimed to evaluate the associations between MetS profiles and TOD in Chinese PA individuals. Methods: Metabolic parameters and pre-clinical TOD including left ventricular hypertrophy, estimated glomerular filtration, and microalbuminuria; insulin sensitivity or resistance; and islet β-cell function were assessed by the homeostasis models (HOMA-IR, HOMA-β) and the other surrogate indexes [composite insulin sensitivity index (ISI), modified β-cell function index (MBCI)] determined from the oral glucose tolerance test were compared in PA vs. matched essential hypertension (EH) patients. Results: A total of 109 PA patients and 109 essential hypertension (EH) controls individually matched for sex, age, and office systolic blood pressure and duration of hypertension were studied. The prevalence of MetS and its individual components in PA was significantly lower than in EH [MetS: 28 (25.6%) vs. 54 (49.5%), P < 0.001]. PA patients had a higher composite ISI but a lower HOMA-IR, HOMA-β, and MBCI than EH controls (all P < 0.05). Concerning TOD, PA patients had significantly higher prevalence of microalbuminuria and left ventricular hypertrophy (LVH), and lower levels of estimated glomerular filtration (eGFR) than EH controls (all P < 0.05). On multivariate logistic regression analysis, female gender and elevated plasma aldosterone levels were significantly associated with TOD in PA. However, there were no significant associations between MetS and its individual components and TOD in PA patients. Conclusions: PA patients had a lower MetS prevalence but exhibited more severe TOD than matched EH controls. The study highlights the deleterious effects of aldosterone excess on the development of TOD, whereas MetS or its individual components might be less influential in PA.